Female mice lacking GluA3 show early onset of hearing loss, cochlear synaptopathy, and afferent terminal swellings in ambient sound levels - Indra Pal; Atri Bhattacharyya; Babak V-Ghaffari; Essence Devine Williams; Maolei Xiao; Mark Allen Rutherford; María Eulalia Rubio (iScience)
Summary: AMPA-type glutamate receptors (AMPARs) mediate excitatory cochlear transmission. However, unique roles of AMPAR subunits are unresolved. Lack of subunit GluA3 (Gria3KO) in male mice reduced cochlear output by 8 postnatal weeks. Here, we studied the role of X-linked Gria3 in cochlear function and synapse anatomy in females. Auditory brainstem responses (ABRs) were similar in 3-week-old female Gria3WT and Gria3KO mice raised in quiet. However, after switching to ambient sound, ABR thresholds were elevated and wave-1 amplitudes were diminished at 5-week and older in Gria3KO. A quiet vivarium precluded this effect. Paired synapses were similar in number, but lone ribbons and ribbonless synapses were more frequent, and swollen afferent terminals were observed only in female Gria3KO mice in ambient sound. Synaptic GluA4:GluA2 ratios increased relative to Gria3WT, particularly in ambient sound, suggesting an activity-dependent increase in calcium-permeable AMPARs in Gria3KO. We propose that lack of GluA3 induces a sex-dependent vulnerability to AMPAR-mediated excitotoxicity.